Prevalencia De Parasitismo Intestinal Y Su Asociacion Con El Estado Nutricional En Niños Del Municipio De Galapa, Atlántico-Colombia - Karen Esther Muñoz Salas; Alma del Socorro Polo Barrios; Carmiña Lucia Vargas Zapata; María del Pilar Garavito Galofre; Carolina Maestre Gonzales; Juan David Rodríguez Macías (European Scientific Journal, ESJ, 2018)
The purpose of this research is to characterize the prevalence of intestinal parasites in children between two to ten years old, and its relation with their nutritional status. 123 children were assessed, from a secondary school in the town of Galapa at the Atlantico department, in the Colombian Caribbean region (Colombia). After informed consent from their parents, after children were weighed and carved, stool samples were collected in triplicate/duplicate. Samples were processed using the sedimentation technique by centrifugation and kato katz. Our results showed parasitism in 39% of the population with a 38% of the individuals infected by protozoa and a 0.8 % with helminths. Analysis by gender showed that there were not statistical significant difference with 20.3% boys were infected compared with 17.1% of the girls. Furthermore, parasites prevalence was not statistically different when analyzed by gender. The parasites with the highest prevalence were: Giardia duodenalis (7.7 %), Blastocystis spp (6.8 %) and Endolimax nana (3.0 %) and children were found infected with polyparasitism by G. duodenalis + Blastocystis spp (1.7 %) y Entamoeba histolytica + Endolimax nana (0.4 %). The children that presented parasitism had a normal size and average weight of 124.8 cm 27.5g respectively. Most children with parasitism had a normal nutritional status (21.1 %), some were overweight (8.1 %) and obesity (4.9 %), and there were no children at risk of thinness and malnutrition. Our findings suggest that there is not significant correlation between the presence of parasites and the dietary habits in this population.